CHEOPS in-flight performance: A comprehensive look at the first 3.5 yr of operations - Fortier, A.; Davies, M.B.; Wolter, D. (Astronomy and Astrophysics, 2024)
Context. Since the discovery of the first exoplanet almost three decades ago, the number of known exoplanets has increased dramatically. By beginning of the 2000s it was clear that dedicated facilities to advance our studies in this field were needed. The CHaracterising ExOPlanet Satellite (CHEOPS) is a space telescope specifically designed to monitor transiting exoplanets orbiting bright stars. In September 2023, CHEOPS completed its nominal mission duration of 3.5 yr and remains in excellent operational conditions. As a testament to this, the mission has been extended until the end of 2026. Aims. Scientific and instrumental data have been collected throughout in-orbit commissioning and nominal operations, enabling a comprehensive analysis of the missiona's performance. In this article, we present the results of this analysis with a twofold goal. First, we aim to inform the scientific community about the present status of the mission and what can be expected as the instrument ages. Secondly, we intend for this publication to serve as a legacy document for future missions, providing insights and lessons learned from the successful operation of CHEOPS. Methods. To evaluate the instrument performance in flight, we developed a comprehensive monitoring and characterisation (M&C) programme. It consists of dedicated observations that allow us to characterise the instrumenta's response and continuously monitor its behaviour. In addition to the standard collection of nominal science and housekeeping data, these observations provide valuable input for detecting, modelling, and correcting instrument systematics, discovering and addressing anomalies, and comparing the instrumenta's actual performance with expectations. Results. The precision of the CHEOPS measurements has enabled the mission objectives to be met and exceeded. The satellitea's performance remains stable and reliable, ensuring accurate data collection throughout its operational life. Careful modelling of the instrumental systematics allows the data quality to be significantly improved during the light curve analysis phase, resulting in more precise scientific measurements. Conclusions. CHEOPS is compliant with the driving scientific requirements of the mission. Although visible, the ageing of the instrument has not affected the missiona's performance. The satellitea's capabilities remain robust, and we are confident that we will continue to acquire high-quality data during the mission extension. © The Authors 2024.
Keywords: Planets and satellites: detection; Planets and satellites: Terrestrial planets; Space vehicles: instruments; Techniques: photometric; Telescopes; C (programming language); Exoplanets; Orbits; Quality control; Space telescopes; Exo-planets; In-flight performance; Mission duration; Performance; Planet and satellite: terrestrial planet; Planets and satellites; Planets and satellites: detections; Terrestrial planets; Satellites